A perspective for identifying intersections among the social, engineering, and geosciences to address water crises - Weems, Carl F.; Poleacovschi, Cristina; Ikuma, Kaoru (Frontiers in Water, 2023)
Reliable access to safe water is essential for health, wellbeing, and livelihoods of people.However, water security innovations benefit when engineering and geoscience decisions consider the systemic human, social, and organizational realities, needs, and goals. Indeed, true innovation that leads to water security requires intensively inclusive and iterative processes to occur at multiple scales of analysis across diverse sciences-for this, expertise and knowledge across the varied sciences is essential to facilitate such convergent, transdisciplinary research. Here, we articulate our perspective for identifying points of intersection and working across disciplinary boundaries to address water crises. Our perspective takes a multidimensional view of community, organization, family, and individual resilience in the face of natural and human hazards. It builds upon previous models of cumulative water related risk by nuancing the relationships amongst levels of analysis, and expanding the idea of cumulative impacts to include interactive impacts (e.g., buffering, enhancing, effects and other moderators), mediated effects (i.e., mechanisms of impact), as well as additive and suppressive linkages amongst risk and protective factors.